Benchmarking of snow water equivalent (SWE) products based on outcomes of the SnowPEx+ Intercomparison Project - L. Mudryk; C. Mortimer; C. Derksen; A. Elias Chereque; P. Kushner (The Cryosphere)
We assess and rank 23 gridded snow water equivalent (SWE) products by implementing a novel evaluation strategy using a new suite of reference data from two cross-validated sources and a series of product intercomparisons. The new reference data combine in situ measurements from both snow courses and airborne gamma measurements. Compared to previous evaluations of gridded products, we have substantially increased the spatial coverage and sample size across North America, and we are able to evaluate product performance across both mountainous and nonmountainous regions. The evaluation strategy we use ranks overall relative product performance while still accounting for individual differences in the ability to represent SWE climatology, variability, and trends. Assessing these gridded products fills an important gap in the literature, since individual gridded products are frequently chosen without prior justification as the basis for evaluating land surface and climate model outputs, along with other climate applications. The top-performing product across the range of tests performed is ERA5-Land, followed by the Crocus snow model. Our evaluation indicates that the accurate representation of hemispheric SWE varies tremendously across the range of products. While most products are able to represent SWE reasonably well across Northern Hemisphere (NH) nonmountainous regions, the ability to accurately represent SWE in mountain regions and to accurately represent historical trends is much more variable. Finally, we demonstrate that, for the ensemble of products evaluated here, attempts to assimilate surface snow observations and/or satellite measurements lead to a deleterious influence on regional snow mass trends, which is an important consideration for how such gridded products are produced and applied in the future.